Hubungan Kadar Troponin T dengan Lama Perawatan dan Mortalitas Selama Perawatan pada Pasien Infark Miokard Akut di RSUD Abdul Wahab Sjahranie Samarinda - Sherin Nadia Khalista; Agustina Rahayu Magdaleni; Diah Purwandini Asmoro (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
In the setting of acute myocardial infarction (AMI), an increased in cardiac biomarker levels is a parameter supporting the diagnosis of AMI. There are several types of cardiac biomarkers, including CK-MB, troponin T, troponin I, LDH, and myoglobin. Troponin is one of the recommended cardiac biomarker owing to its high specificity. Besides indicating the occurrence of AMI, troponin T is also known to have an association with ischemic duration, degree of ischemia, extent of infarction, complications, and even mortality among AMI patients. These parameters are thought to be the factors that influence the length of stay and in-hospital mortality in AMI patients. Therefore, the author was interested to determine the relationship between troponin T levels with treatment duration and in-hospital mortality in AMI patients. This analytical study was conducted using cross-sectional approach and secondary data. The study samples are AMI patients treated at Abdul Wahab Sjahranie Hospital in Samarinda between January 1, 2018 - December 31, 2018 who met the inclusion and exclusion criteria. In total, this study involved 86 people. The results show that the average troponin T levels in AMI patients is 1159.93 pg/ml, the average length of stay is 5.11 days, and the percentage of mortality during treatment is 10.5%. Bivariate analysis shows that troponin T does not have a significant relationship with length of stay (p = 0.422) and in-hospital mortality (p = 1,000). Thus, it can be concluded that troponin T levels are not associated with length of stay and in-hospital mortality in AMI patients. Keywords : AMI, Troponin T levels, Length of Stay, In-Hospital Mortality